Applying Service Dominant Logic in Two Wheeler Industry in India: Measuring the Impact of Service Dominant Logic in the Two Wheeler Industry in India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Marketing has shifted its perspective from goods centred logic to service dominated approach with high emphasis on benefits derived from service quality. Service dominant orientation has been known to impact business firms due to their benefits in the form of performance outcomes. With advancement in marketing literature, the term service dominant logic has progressed to be called as service dominant orientation emphasising on co-creation of value and treating the firm and consumers as resource integrators. This service dominant approach of marketing is also the new dominant logic for marketing today. Service dominant logic is based on certain foundational premises which explain the concept in detail. Over the past few years, India has emerged as the most preferred location for manufacturing of vehicles and other automotive components. In terms of global rankings in manufacturing output, India is presently second largest in case of two wheeler segment. The study aimed to measure service dominant orientation in two wheeler industry in India, to analyse the factors contributing to service dominant orientation in two wheeler industry in India and to study the relationship between service dominant orientation and demographic variables in two wheeler industry in India. Cramer’s V and factor analysis were used to analyse the data. The results indicated that applying service dominant logic in marketing practices today is a quintessential phenomenon and improves the quality of buyer seller interaction.